Cycloaddition reactions of titanium and zirconium imido, oxo and hydrazido complexes supported by tetraaza macrocyclic ligands - Blake, A; McInnes, J; Mountford, P; Nikonov, G; Swallow, D; Watkin, D (1999)
The tetraaza macrocycle-supported titanium and zirconium imido complexes [Ti(NR)(Me ntaa)] [R = Bu t, Ph. Tol or 4-C 6H 4NO 2; n = 4 or 8 where H 2Me ntaa = tetra- or octa-methyldibenzotetraaza[14]annulene, respectively] and [Zr(NC 6H 3Pr i2-2,6)(py)(Me 4taa)] react with isocyanates or carbon dioxide to form cycloaddition products generally of the type [M {N(R)C(O)E}(Me ntaa)] (M = Ti or Zr, R = aryl or tert-butyl, E = O, NBu t or N-aryl). The complex [Zr{N(C 6H 3Pr i2-2,6)C(O)N(Bu t)}(Me 4taa)] is also formed by reaction of the bis(arylimide) [Zr(NHC 6H 3Pr i-2,6) 2-(Me 4taa)] with Bu tNCO. The crystal structures of [Ti{N(Tol)C(O)O}(Me 4taa)] (Tol = p-tolyl) and [Zr{N(C 6H 3Pr i2-2,6)C(O)N(Bu t)}(Me 4taa)] are described. The tert-butyl imido complexes [Ti(NBu t)(Me ntaa)] (n = 4 or 8) react with Ph 2NNH 2 to give the corresponding terminal N,N-diphenylhydrazido derivatives [Ti(NNPh 2)(Me ntaa)] and these yield the cycloaddition products [Ti{N(NPh 2)C(O)O}(Me ntaa)] or [Ti{N(NPh 2)C(O)N(Tol)}(Me 4taa)] with CO 2 or TolNCO, respectively. The related titanium oxo complexes [Ti(O)(Me ntaa)] (n = 4 or 8) react with p-tolyl isocyanate to form the N,O-carbamate products [Ti{N(Tol)C(O)O}(Mentaa)], and with ditolylcarbodiimide to form the N,N-ureate derivative [Ti{N(Ph)C(O)N(Ph)}(Me ntaa)] in which complete rupture of the Ti=O linkage has occurred. Reaction of the N-phenyl-N-tolyl (asymmetric) ureate [Ti{N(Ph)C(O)N(Tol)}(Me 4taa)] with an excess of PhNCO gave quantitative conversion to the N,N-symmetric product [Ti{N(Ph)C(O)N(Ph)}(Me 4taa)] and TolNCO. Crossover NMR tube experiments suggest that this reaction occurs via an associative mechanism.